Laços relacionais no varejo supermercadista - Arraes, Vívian Larissa Alves Araújo (2019)
This study aims to analyze the ties that influence the consumer relationship between customer and retail supermarket in the context of a medium-sized city. This research is based on the relationship marketing literature, with emphasis on the theory of relational bonds, which bases the assumptions and delineates the qualitative research, seeking to meet the objectives it proposes. To do so, a multiple case study was performed in combination, using as methods of applying the empirical research the participant observations, conducted in the supermarkets stores of each case study, and the semi-structured interviews, carried out with regular clients of the companies investigated. Among the results found, it was possible to highlight the types of bonds that stood out the most in the context: being the socio-emotional, psychological and cultural, operational and environmental bonds where the ones that presented the greatest positive strength. It was also observed that the types of relational ties work together, when it was necessary to develop the aspects of each one of them to positively influence the relationship between consumer and company. Thus, the greatest finding of this research was obtained, referring to the identification of “interlaces”, which act in the union of the types of relational ties that have the greatest positive force in the context. These links, called "Belonging" and "Shopping Experience", have shown great influence for the development of loyalty categories. Therefore, this study has contributed to the relationship marketing literature, from the expansion of research on relational ties in the retail context. In addition, from the results presented, it was possible to suggest managerial contributions to the supermarket retailer in the context of the research, as well as to point out directions for similar studies on relationships in the retail context, in other cities or segments. In this way, it collaborates with the strengthening of the market and the deepening of theoretical studies on retail.